How responsive is the labor market to tax policy? - Richard Blundell (IZA World of Labor, 2014)
With aging populations and increased demands on government revenue, countries need to boost employment and earnings. Tax policy should focus on labor market entry and retirement. Those are the points where labor supply is most responsive to tax incentives, which can enhance the flow into work of people leaving school and women with young children and can prolong employment among older workers. Human capital policy has a complementary role in improving the payoff to work and ensuring that earnings hold up longer over a lifetime.
Keywords: J2; J3; 330; work; employment; tax incentives; human capital